Conjugated linoleic acid in meat - Govari, M; Vareltzis, P (Journal of the Hellenic Veterinary Medical Society, 2024)
Conjugated linoleic acid (CLA) consists of a group of geometric and positional isomers of linoleic acid. According to various studies, CLA has beneficial health effects against cancer, atherosclerosis, diabetes, obesity, cardiovascular malfunction, or enhance immune function. The most important isomers of CLA found in meat are cis-9, trans-11 CLA and the trans-10, cis-12 CLA. Naturally occurring CLA originates mainly from bacterial isomerisation as well as biohydrogenation of polyunsaturated fatty acids (PUFA) in the rumen in ruminant animals and endogenous formation from desaturation of trans-fatty acids in the tissues of monogastric as well as ruminant animals. Several factors such as seasonal variations, animal breeds, management or diet are influencing the CLA content in meat. In ruminants, the CLA content in meat is usually higher than this of monogatric animals or chicken. The CLA content in beef and lamb is usually found above 1 mg/g fat, while in pork, horse and chicken meat is usually found lower than 1 mg/g fat. The storage (refrigeration or freezing) as well thermal processing such as cooking seems to have no effect on CLA content of meat.